2011
DOI: 10.1200/jco.2010.33.3757
|View full text |Cite
|
Sign up to set email alerts
|

Relative Abundance of EGFR Mutations Predicts Benefit From Gefitinib Treatment for Advanced Non–Small-Cell Lung Cancer

Abstract: The relative EGFR mutation abundance could predict benefit from EGFR-TKI treatment for advanced NSCLC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
174
2
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 216 publications
(187 citation statements)
references
References 23 publications
10
174
2
1
Order By: Relevance
“…Differences in overall survival and objective response rate in patients with high and low abundances of EGFR mutations were not significant. 227 This study also pointed out that heterogeneity caused by factors other than EGFR mutation could also affect EGFR TKI response. Sharma et al 228 reported detecting a small subpopulation of reversibly 'drug-tolerant' cells showing more than 100-fold reduced drug sensitivity.…”
Section: Other Genomic Alterationsmentioning
confidence: 74%
“…Differences in overall survival and objective response rate in patients with high and low abundances of EGFR mutations were not significant. 227 This study also pointed out that heterogeneity caused by factors other than EGFR mutation could also affect EGFR TKI response. Sharma et al 228 reported detecting a small subpopulation of reversibly 'drug-tolerant' cells showing more than 100-fold reduced drug sensitivity.…”
Section: Other Genomic Alterationsmentioning
confidence: 74%
“…The results of the present study indicate that EGFR mutations detected in both the tissue and plasma (B+/T+) was better for predicting the benefit from first-line EGFR-TKI treatment in advanced NSCLC, compared with detection in a single specimen. Recent studies that investigated the effect of intratumor EGFR mutation heterogeneity on clinical outcomes following EGFR-TKI therapy have demonstrated that an increased abundance of intratumoral EGFR mutations (implying low heterogeneity) may lead to improved clinical outcomes compared to a low abundance of EGFR mutations (20). Although the release mechanism of ctDNA from tumor tissues to peripheral blood is not well understood, ctDNA is likely derived from apoptotic and necrotic tumor cells, including primary tumors, metastatic lesions or circulating tumor cells (21).…”
Section: Discussionmentioning
confidence: 99%
“…Karachaliou et al (14) reported that in the patients with tumor tissue EGFR mutation, serum ex19del detected was a positive predictor for OS compared with non-serum ex19del detected patients treated with erlotinib, while serum L858R mutation was the opposite, confirming the difference between L858R mutation and ex19del (21). In a study by Zhou et al (13), high EGFR mutation abundance in tumor tissue, defined as positive in the ARMS test and gene sequencing, possessed predictive significance for benefit from gefitinib treatment for patients with NSCLC. These results revealed a similar clinical value of qualitative EGFR gene mutation status in blood compared with that in tumor tissue samples.…”
Section: Discussionmentioning
confidence: 91%
“…Theoretically, plasma EGFR mutation concentration should be associated with the EGFR mutation abundance in tumor tissues, tumor burden, and tumor necrosis or apoptosis, since tumor lysis has been considered as the main source of the cfDNA found in peripheral blood (11,12). Zhou et al (13) reported that high EGFR mutation abundance in tumor tissue, which was defined as positivity in the amplification refractory mutation system (ARMS) test and gene sequencing, predicted improved responsiveness in patients with NSCLC to gefitinib treatment. Data from the EURTAC trial demonstrated that in patients with tissue EGFR mutation, qualitatively detected L858R mutation in cfDNA, using the TaqMan assay, indicated poor overall survival (OS) while ex19del acted inversely (14).…”
Section: Association Of Mutant Egfr L858r and Exon 19 Concentration Imentioning
confidence: 99%